Предмет: Алгебра,
автор: SergeySuperr
Решите задачу №1, срочно, 40б, лучше с объяснением
Приложения:
Ответы
Автор ответа:
1
y=(k-1)x-2k
M(6;0)
по условию M ∈ y(x)
⇒ 0=(k-1)*6-2k
6k-6-2k=0
4k=6
k=1.5
Ответ: 1.5
M(6;0)
по условию M ∈ y(x)
⇒ 0=(k-1)*6-2k
6k-6-2k=0
4k=6
k=1.5
Ответ: 1.5
SergeySuperr:
Спасибо, скоро будут ещё задачи))
Похожие вопросы
Предмет: Математика,
автор: sofiaolivia
Предмет: Алгебра,
автор: olkzkxll
Предмет: Русский язык,
автор: zovimenyakrutoy228
Предмет: Алгебра,
автор: Аноним
Предмет: Химия,
автор: камилав